Characterization of E‐NTPDase (EC 3.6.1.5) activity in hepatic lymphocytes: A different activity profile from peripheral lymphocytes. (19th February 2017) - Doleski, Pedro H.; Adefegha, Stephen A.; Cabral, Fernanda L.; Leal, Daniela B.R.
Abstract : The activity of ectonucleoside triphosphate diphosphohydrolase (E‐NTPDase; EC 3.6.1.5) was characterized in hepatic lymphocytes (HL) of rats. For this purpose, a specific method for the isolation of lymphocytes from hepatic tissue was developed. Subsequently, E‐NTPDase activity of rat HL was compared with that of rat peripheral lymphocytes. The HL showed high cell count and viability. Also, the characterization test revealed that the optimal E‐NTPDase activities were attained at 37°C and pH 8.0 in the presence of Ca 2+ . In addition, in the presence of specific E‐NTPDase inhibitors (20mM sodium azide and 0.3mM suramin), there were significant inhibitions in nucleotide hydrolysis. However, there was no significant change in adenosine triphosphate (ATP) or adenosine diphosphate (ADP) hydrolysis in the presence of inhibitors of other E‐ATPase (0.1mM Ouabain, 0.5mM orthovanadate, and 1mM, 5mM, and 10mM sodium azide). Furthermore, the kinetic behavior of the enzyme in HL showed apparent K m of 134.90 ± 0.03μM and 214.40 ± 0.06μM as well as V max of 345.0 ± 28.32 and 242.0 ± 27.55 ƞmol Pi/min/mg of protein for ATP and ADP, respectively. The Chevillard plot revealed that ATP and ADP were hydrolyzed at the same active site of the enzyme. Our results suggest that the degradation of extracellular nucleotides in HL may have been primarily accomplished by E‐NTPDase. The higher E‐NTPDase activity observed in HL may be attributed to the important physiological functions of ATP and ADP in HL. Significance of the study: Extracellular purine nucleotides are able to interact with specific receptors and trigger a number of important physiological functions in cells. This interaction is controlled by ectonucleoside triphosphate diphosphohydrolase (E‐NTPDase), enzyme that present their catalytic site at the extracellular space and degrades nucleotides. This purinergic signaling has important functions in peripheral lymphocytes and may represent an important new therapeutic target for the treatment of immunological diseases. However, there is dearth of information on the involvement of E‐NTPDase in liver lymphocytes. The liver is an important organ, which performs both metabolic and toxicological roles in living organism, and hepatic lymphocytes may play crucial action in the regulation of immune responses in the liver tissue. Furthermore, various chronic diseases such as cirrhosis may be treated with novel pharmacotherapy by targeting the modulation of hepatic lymphocytes. Thus, the significance of this study is to evaluate the activity of E‐NTPDase in liver lymphocyte and compare its activity with the peripheral lymphocytes.